Characterization of bovine serum albumin immobilization on surface modified glass slides in case of pyro-electrohydrodynamic spots - Concetta Di Natale; Sara Coppola; Veronica Vespini; Volodymyr Tkachenko; Giuseppina Luciani; Giuseppe Vitiello; Francesca Ferranti; Silvia Mari; Pier Luca Maffettone; Simonetta Grilli (Analytica Chimica Acta, 2024)

Impact of two new non-conventional yeasts, Candida oleophila and Starmerella lactis-condensi, isolated from sugar-rich substrates, on Frappato wine aroma - Nicola Francesca; Vincenzo Naselli; Rosario Prestianni; Antonino Pirrone; Enrico Viola; Raffaele Guzzon; Luca Settanni; Antonella Maggio; Alessandro Vaglica; Maurizio Bruno; Luciano Gristina; Daniele Oliva; et al. (Food Bioscience, 2024)

Assessment of arsenic mobility in a shallow aquifer from Bevera Valley Basin (Northern Italy) - Giuseppe Sappa; Maurizio Barbieri; Francesca Andrei; Flavia Ferranti (Arabian Journal of Geosciences, 2019)

Effect of formulated diets on the proximate composition and fatty acid profiles of sea urchin Paracentrotus lividus gonad - Ermelinda Prato; Mariachiara Chiantore; Maeve S. Kelly; Adam D. Hughes; Philip James; Maria Paola Ferranti; Francesca Biandolino; Isabella Parlapiano; Benedetto Sicuro; Giovanni Fanelli (Aquaculture International, 2018)

Managing climate change in conservation practice: an exploration of the science–management interface in beech forest management - Jessica de Koning; Esther Turnhout; Georg Winkel; Marieke Blondet; Lars Borras; Francesca Ferranti; Maria Geitzenauer; Metodi Sotirov; Alistair Jump (Biodiversity and Conservation, 2014)
Scientific studies reveal significant consequences of climate change for nature, from ecosystems to individual species. Such studies are important factors in policy decisions on forest conservation and management in Europe. However, while research has shown that climate change research start to impact on European conservation policies like Natura 2000, climate change information has yet to translate into management practices. This article contributes to the on-going debates about science–society relations and knowledge utilization by exploring and analysing the interface between scientific knowledge and forest management practice. We focus specifically on climate change debates in conservation policy and on how managers of forest areas in Europe perceive and use climate change ecology. Our findings show that forest managers do not necessarily deny the potential importance of climate change for their management practices, at least in the future, but have reservations about the current usefulness of available knowledge for their own areas and circumstances. This suggests that the science–management interface is not as politicized as current policy debates about climate change and that the use of climate change ecology is situated in practice. We conclude the article by discussing what forms of knowledge may enable responsible and future oriented management in practice focusing specifically on the role of reflexive experimentation and monitoring.

WCI, a novel wheat chymotrypsin inhibitor: purification, primary structure, inhibitory properties and heterologous expression - Antimo Di Maro; Francesca Farisei; Daniela Panichi; Valeria Severino; Natalia Bruni; Anna Grazia Ficca; Pasquale Ferranti; Valeria Capuzzi; Francesca Tedeschi; Elia Poerio (Planta, 2011)

Purification and characterization of Alpha-Fetoprotein from the human hepatoblastoma HepG2 cell line in serum-free medium - Patrizia Carlini; Pasquale Ferranti; Francesca Polizio; Maria R. Ciriolo; Giuseppe Rotilio (BioMetals, 2007)